PREVENTABILITY OF DENTAL DISEASES - Hamdamova Lola Zarifovna (Ustozlar uchun, 2025)
Numerous studies prove that the dental status of the Russian population has a steady tendency to deteriorate (Kuzmina E.M., 2001; V.I. Starodubov, K.G. Dzugaev, A.A. Kalininskaya, 2006; D.G. Meshcheryakov, 2006; V.G. Butova, 2008). Already at the age of fifteen, 91.9% of schoolchildren suffer from caries (E.G. Semenchenko, 2006). Every year in Russia there are cases of death due to diseases of the teeth and oral cavity (S.T. Sokhov, S.M. Airapetyan, T.P. Sabgaida, 2009).